Risk Analysis and Alert System for CBRN Threats: Features and Functions - Zbigniew TARAPATA; Ryszard ANTKIEWICZ; Andrzej NAJGEBAUER; Dariusz PIERZCHAŁA (Communications of International Proceedings, 2021)
The paper presents a system (WAZkA) supporting risk analyses of CBRN threats and alarming the population, for the purpose of the National System for Detection of Contamination and Alarming in Poland. Additionally, the article presents the point of designing such a system, its concept, components, features, and functions. The selected modules included in the WAZkA system: Event Tree Analyzer, Simulators of Threats Causes and Effects and Emulators of Threats Monitoring Systems are described. The idea of using the system for the purpose of training, including the designed emulators of the risk monitoring systems is presented, too. The above approach significantly facilitates the organization of training and learning about rare situations or situations that have never occurred, but that are potentially dangerous. The method of integration with Regional Warning System (RSO) and IP sirens is also described.
Keywords: CBRN risk analysis; event tree analyzer; human losses calculation; threats visualization; warning and alerting population; IT system WAZkA.